Morphological features of basivertebral foramen among different age groups: Recognition in spine - Wang, Qiang; Jin, Benyu; Zhang, Jianfeng (Frontiers in Surgery, 2023)
Abstract Background: Basivertebral foramen (BF) is a vessel and nerve passage in the posterior wall of vertebral body (VB). Our goal was to report BF’s morphological characteristics in different age groups of mainland Chinese adults and to evaluate the relationship between BF’s morphology and factors such as age, gender, heavy work, size and level of VB. Methods: We enrolled 300 adults among persons who came to our hospital for health examination. We measured BFs and VBs’ parameters on T1 weighted sagittal lumbar spine MR images. We also assessed following potential predictors: gender, body height, body weight, body mass index, alcohol use, habits of smoking and drinking, type of work (physical work or non-physical work). A stepwise multivariate linear regression analysis was conducted to identify predictors of BF’s height. Results: People above 60 have significantly bigger BFHr than those in young adulthood and in the middle ages at all five levels, while they have shallowest BFs, especially at L3. Multiple linear regression resulted in a formula that accounted for 30.1% of the variability in the height of basivertebral foramen. Significant predictors included: gender, age, level, vertebral height and heavy work. Conclusions: Age is the highest weight in all factors on the height of BF. BF is closer to the upper endplate. The BF was relatively higher and deeper in the female lumbar spine. Heavywork results in lower BF. Last but not the least, as we supposed, BF gets shallower and higher compare to VB with age. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.